Media Kampanye untuk Perubahan Kebijakan Melalui Video: Pembelajaran Dari Desa Lakardowo - Rahardian, Ramaditya; Mediyastuti Sofyan, Meti; Maulana Yusup, Rikki; Andri, Yayan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The article in this research is to describe a series of advocacy processes carried out by Civil Society Organizations (CSOs) and Non-Governmental Organizations (NGOs) in fighting for the right to a healthy environment to reject the existence of hazardous and toxic waste processing industries in Lakardowo village, District Jetis, Mojokerto Regency with social media platforms such as online videos on YouTube as a means of struggle. Qualitative approach is used in this research, meanwhile data collection technique is done by in-depth interview and documentation technique. The technique of determining informants is by purposive sampling. The results of the study show that advocacy carried out by Civil Society Organizations (CSOs) and Non-Governmental Organizations (NGOs) has been able to influence public awareness at large and provide support for advocacy carried out, but for changes in environmental permit policies to date have not been able to change policies that have been implemented have been made by existing policy makers.